Responsibilities of a Notary in Concerning Making an Authentic Deed Based on Falsification of Letters by One of the Parties - Farman Riantama Budi; Aryani Witasari; Ngadino Ngadino (Sultan Agung Notary Law Review, 2021)
This research aims to know the responsibilities of the notary in the event of letter forgery by the parties in making the authentic deed and whether a notary can be held responsible for a criminal case if a loss occurs to one of the parties as a result of a false document from one of the parties. The approach method in this research is empirical juridical method. The specification of this research is descriptive analytic. The data in this study are primary data and secondary data. These problems are analyzed using the theory of authority, theory of legal responsibility. Based on the results of that research when a Notary in carrying out his position is proven to have committed a violation, then the Notary is responsible according to his actions, both in terms of Administrative Law, Civil Law, namely in accordance with the provisions of the sanctions contained in Articles 84 and 85 of the Law on Amendments to the Law on the Position of Notary Public and code of conduct. A notary cannot be held responsible for a criminal case if there is a loss to one of the parties as a result of a false document from one of the parties, because the notary only records what is conveyed by the parties to be put into deeds false information submitted by the parties is the responsibility of the parties. In other words, what can be accountable to the Notary is if the fraud or deception originates from the Notary himself.